A Application of Correlation Analysis to the increase in fuel prices on inflation in Indonesia - Muthahharah, Isma (Journal of Mathematics: Theory and Applications, 2025)
Fuel is one of the products that can be traded from oil and gas natural resources. The increase in fuel prices has caused a decrease in people's purchasing power and also greatly affects demand and supply. The purpose of this study is to observe the effect of changes in the price of fuel oil (BBM), especially the type of Pertamax, on the inflation rate in Indonesia in the period March 2020 to March 2024. Fuel price data is sourced from Pertamina reports, while inflation rate data is obtained from Bank Indonesia reports. The type of research conducted is quantitative research. The results showed that the Spearman correlation analysis between the Inflation and Fuel variables in Indonesia during the period March 2020 to March 2024 showed a strong and statistically significant positive relationship between the two. It is concluded that when the price of Pertamax fuel increases, the inflation rate tends to also increase, and vice versa.